MANAJEMEN SARANA DAN PRASARANA UNTUK MENINGKATKAN MUTU PENDIDIKAN DI SMPN 1 SUBANG: SYSTEMATIC LITERATURE REVIEW - Sutisna, Asep; Kurniawan, Rudi; Rosmaladewi, Okke (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the management of educational facilities and infrastructure in improving the quality of education through the Systematic Literature Review (SLR) method. This research examines 30 scientific articles consisting of 20 national journals and 10 international journals published within the last five years. The SLR process was conducted through the stages of identification, screening, eligibility, and inclusion in accordance with the PRISMA procedure. The findings indicate that facilities and infrastructure management—covering planning, procurement, inventory management, maintenance, and supervision—has a significant influence on improving the quality of education, particularly in enhancing learning effectiveness, student achievement, and the quality of educational services. The analysis also identifies the presence of a theoretical gap, phenomenal gap, and research gap in studies related to educational facilities and infrastructure management. The state of the art of this research lies in integrating facilities and infrastructure management with educational quality through an SLR approach. The novelty of this study is the development of a conceptual model of facilities and infrastructure management based on educational quality improvement.